1986
DOI: 10.1111/j.1751-0813.1986.tb02951.x
|View full text |Cite
|
Sign up to set email alerts
|

Survey of anthelmintic resistance in Western Australian sheep flocks 2. Relationship with sheep management and parasite control practices

Abstract: Owners of 116 farms, whose flocks had been tested for anthelmintic resistance, were interviewed to determine their use of various sheep management and parasite control practices and their knowledge and adoption of recommended procedures for the prevention and control of resistance. Farmers knowledge of current recommendations related mainly to changing drenches and drench groups. Other aspects of the recommended program including reduction of drenching frequency and the use of alternative management strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Generally, the Danish treatment frequencies are low compared with countries with high AR levels, such as South Africa [48], New Zealand and Australia [10, 27], and high treatment frequencies are probably not the major cause of AR in Denmark today. A further reduction of the treatment frequency, as recommended to limit AR development [2, 15], will be hard to implement under Danish circumstances, and is not considered realistic.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the Danish treatment frequencies are low compared with countries with high AR levels, such as South Africa [48], New Zealand and Australia [10, 27], and high treatment frequencies are probably not the major cause of AR in Denmark today. A further reduction of the treatment frequency, as recommended to limit AR development [2, 15], will be hard to implement under Danish circumstances, and is not considered realistic.…”
Section: Discussionmentioning
confidence: 99%
“…Underdosing is generally considered an important factor in the development of AR (Edwards et al, 1986) because sub therapeutic doses might allow the survival of heterozygous resistant worms (Smith, 1990). Several laboratory experiments have shown that underdosing contributes to the selection of resistant or tolerant strains (Egerton et al, 1988;Hoekstra et al, 1997).…”
Section: Use Of Anthelmintics In Sub-optimal Dosesmentioning
confidence: 99%
“…II) are now recommended for treating goats with most anthelmintics [22]. Under-dosing caused by the under-estimation of the animal's weight is nothing less than anecdotal since epidemiological surveys mention that bodyweights of sheep and goats are estimated by the eye [8,36,67,68,83,100], and that anthelmintic doses are not calculated for the heaviest animals of the flock [32,67,68,83,100]. In French dairy goat herds, the bodyweight of goats was usually evaluated at more or less 50 kg in the 1980s [17] which grossly under-estimated the real weight of the goats.…”
Section: Under-dosingmentioning
confidence: 99%
“…The main factor evoked to select for resistance concerns treatment frequency and, "a large number of anthelmintic treatments with the same anthelmintic family for years" is taken as the key factor for selecting for resistance [91]. This statement is supported by surveys realised on a regional scale, in New Zealand [59,83]; in Malaysia [33]; in South Africa [95]; in the United Kingdom [53,75]; in Australia [36,72]. The "same" repeated anthelmintic treatment is a major cause, in experimental and oversimplified conditions (three-month-old lambs, synchronous infestation with only one to three gastro-intestinal nematode species...) of positive correlation between intensity of resistance and treatment frequency [5,66,71].…”
Section: Introductionmentioning
confidence: 99%